Anterior gradient protein 3 is associated with less aggressive tumors and better outcome of breast cancer patients - Obacz, Joanna; Brychtova, Veronika; Podhorec, Jan; Fabian, Pavel; Dobes, Petr; Vojtesek, Borivoj; Hrstka, Roman (OncoTargets and therapy, 2015)
Anterior gradient protein (AGR) 3 is a highly related homologue of pro-oncogenic AGR2 and belongs to the family of protein disulfide isomerases. Although AGR3 was found in breast, ovary, prostate, and liver cancer, it remains of yet poorly defined function in tumorigenesis. This study aimed to determine AGR3 expression in a cohort of 129 primary breast carcinomas and evaluate the clinical and prognostic significance of AGR3 in these tumors. The immunohistochemical analysis revealed the presence of AGR3 staining to varying degrees in 80% of analyzed specimens. The percentage of AGR3-positive cells significantly correlated with estrogen receptor, progesterone receptor (both P<0.0001) as well as low histological grade (P=0.003), and inversely correlated with the level of Ki-67 expression (P<0.0001). In the whole cohort, AGR3 expression was associated with longer progression-free survival (PFS), whereas AGR3-positive subgroup of low-histological grade tumors showed both significantly longer PFS and overall survival. In conclusion, AGR3 is associated with the level of differentiation, slowly proliferating tumors, and more favorable prognosis of breast cancer patients.
Keywords: protein disulfide isomerase; ER-positive breast cancer; AGR3; immuno histochemistry; patient survival